Environmental potential of the physical and geographical regions of Belarus and its significance for the national ecological network - Bryleuski, Mikhail N. (Journal of the Belarusian State University. Geography and Geology, 2023)
The results of a study of the environmental potential of the physical and geographical regions of Belarus of the rank of provinces, districts and regions, on which the formation of a national ecological network depends, are presented. Changes have been made to the scheme of physical and geographical zoning of the country, the boundaries and areas of physical and geographical regions have been clarified. It has been established that the assessment of the environmental potential should be carried out by physical and geographical regions, since they differ significantly in the presence of natural frame lands, the number and area of specially protected natural areas. A method for determining the environmental potential is proposed as an integral indicator of the index of preservation of natural geosystems and the coefficient of provision of specially protected natural areas. Calculations have shown that the index of conservation of natural geosystems varies from 0.58 (Kopyl Ridge) to 1.40 (Lelchitsa Plain), and all physical and geographical regions were differentiated into four groups according to this indicator. The physical and geographical regions were also divided into four groups according to the value of the coefficient of provision with specially protected natural areas. The coefficient reaches its maximum values in 5 physical and geographical regions with reserves and national parks. The integral indicator of the environmental potential in the territory of Belarus varies from 0.58 (Kopyl Ridge) to 2.06 (Upper Berezina Lowland). The physical and geographical regions were divided into seven groups according to the magnitude of their environmental potential. It has been established that in recent years there has been an increase in the conservation potential of most physical and geographical regions due to the growth in the area of natural frame land and the increase in the area of specially protected natural areas.